Cutaneous Adverse Events in Newly Approved FDA Non-cancer Drugs: A Systematic Review - Paul C. Macklis; Brittany Dulmage; Brady Evans; Misha Rosenbach; Johann E. Gudjonsson; Benjamin H. Kaffenberger (Adis, Springer Healthcare, 2020)
Abstract The prevalence of cutaneous adverse events attributable to newly approved anti-cancer drugs has been well reviewed in the dermatologic literature. In contrast, over 75% of US Food and Drug Administration approvals in the past 5 years have been for non-cancer drugs and indications. This represents multiple other categories of approved medications associated with cutaneous adverse reactions. To investigate the cutaneous adverse events associated with these potentially neglected medications, a systematic review was conducted. Two hundred and forty-one medications approved by the Food and Drug Administration between 2013 and 2018 were reviewed and 180 non-oncologic drugs were identified. The prescribing information for each medication was reviewed for the presence of cutaneous adverse events and a supplemental literature search was performed to better characterize any adverse events outlined within the prescribing information. Most reactions were classified as morbilliform, macular, popular, or maculopapular. Fortunately, only a few severe cutaneous adverse reactions were reported, namely in benznidazole, cannabidiol, and sofosbuvir. This review summarizes available data drawn from clinical trials and case reports involving cutaneous adverse events from the 21 non-oncologic medications associated with cutaneous adverse events.